1986
DOI: 10.1128/jb.168.3.1422-1429.1986
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of a murein-membrane attachment site fraction when cell division is blocked in lkyD and cha mutants of Salmonella typhimurium and Escherichia coli

Abstract: Membrane fractionation studies were performed on Salmonella typhimurium lkyD(Ts) and E. coli cha (Ts) mutants that appeared to be blocked at a late stage of the cell division cycle. In both cases growth of the mutant strains at nonpermissive temperatures was associated with accumulation of a characteristic cell envelope fraction (fraction OML) that contained inner membrane, murein, and outer membrane components. The isolated fraction corresponded in composition and buoyant density to a fraction from wild-ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1989
1989
2013
2013

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…There appears to be a general correspondence of mutations in proteins involved in cell division and large circular structures emanating from the septum [55, 80, 81]. Although these structures have been labeled as “OMVs,” their size and site of budding are not what we typically see for OMVs produced by wild-type Gram-negative bacteria.…”
Section: Palmentioning
confidence: 99%
See 1 more Smart Citation
“…There appears to be a general correspondence of mutations in proteins involved in cell division and large circular structures emanating from the septum [55, 80, 81]. Although these structures have been labeled as “OMVs,” their size and site of budding are not what we typically see for OMVs produced by wild-type Gram-negative bacteria.…”
Section: Palmentioning
confidence: 99%
“…Besides its role in envelope stability, the Tol–Pal complex has been shown to aid in OM invagination during the constriction phase of cell division. , There appears to be a general correspondence of mutations in proteins involved in cell division and large circular structures emanating from the septum. ,, Although these structures have been labeled as “OMVs”, their size and site of budding are not what we typically see for OMVs produced by wild-type Gram-negative bacteria. Consequently, defining how Pal plays potentially separate roles in cell division and OMV production provides a challenge in the field.…”
Section: Palmentioning
confidence: 99%
“…It was previously shown that the OML fraction accumulates to high levels in certain cell division mutants of E. coli and Salmonella typhimurium (cha and lkyD, respectively) that are blocked at a late stage of the division process (5 On the other hand, studies of the development of periseptal annuli have shown that new annuli are generated early in the division cycle (6). The annuli appear to continue their growth around the cylinder during much of the remainder of the cycle, during and after displacement to their final locations within the cell (6,7).…”
mentioning
confidence: 99%